CURRENCY REGULATION AND CURRENCY CONTROL MECHANISM AS AN INTERNATIONAL ECONOMIC ACTIVITY EFFICIENCY TOOL - Modenov, Anatoly; Semenova, Anna; Lelyavina, Tatiana (Revista Inclusiones, 2020)
Economic relations efficiency enhancement and international relations settlement shall be based on historical experience. Scientists and experts seek for new ways of how to improve international relations and strengthen links on the world financial market without using accumulated experience. The authors offer to consider some current issues of currency regulation and currency control from the perspective of historical experience. Historical aspects of currency regulations were defined; the paradigm of currency relations, currency system, currency market, currency regulations and currency control was considered as primary tools of the governmental monetary and financial policy. Currency regulation system was examined and its elements were specified. It was established that in case of currency control slackening in the process of the currency regulation the investment flows drop resulting in decrease of activity of the parties to the real economy, which leads to decline in the international economic activity figures.